Hesitancy In Getting COVID-19 Vaccine – An Alarming Concern - Riaz Ahmed (Journal of Rawalpindi Medical College, 2021)
According to new research, health care workers and medical students are reluctant to receive vaccinations. This recent research found that hesitancy was often observed in age groups. This obstacle, though, does not prevent medical personnel from caring for virus-infected patients. With the appropriate education and advice, apprehension and anxiety will be substituted by confidence in the battle against coronavirus disease.